2007
DOI: 10.1080/15602210701725272
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the self-evaluation skills of first year pharmacy students

Abstract: Introduction: Self-evaluation is an important skill in many fields of endeavour, including education and learning. Health-care workers, e.g. pharmacists, have a particular need to develop this skill. We therefore investigated the self-evaluation skills of several cohorts of pharmacy undergraduates during the first year of their course. Students were asked to predict their end of first year and end of course results, and these predictions were compared with their actual marks.Methods: A wide-ranging questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…13 In addition, many preceptors had the added responsibility of running a business, which may have caused a conflict of interest, and they may have perceived competence from a different perspective. 10 More preceptors perceived graduates to be competent in dispensing a prescription than in extemporaneous compounding, which was the competence rated lowest by all 3 groups of respondents. This may have been due to compounding skills being taught in the junior years (years 1 and 2) of the 4-year program, while counselling and dispensing of proprietary products and aseptic/sterile compounding were the focus of dispensing in senior years.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…13 In addition, many preceptors had the added responsibility of running a business, which may have caused a conflict of interest, and they may have perceived competence from a different perspective. 10 More preceptors perceived graduates to be competent in dispensing a prescription than in extemporaneous compounding, which was the competence rated lowest by all 3 groups of respondents. This may have been due to compounding skills being taught in the junior years (years 1 and 2) of the 4-year program, while counselling and dispensing of proprietary products and aseptic/sterile compounding were the focus of dispensing in senior years.…”
Section: Discussionmentioning
confidence: 93%
“…9 In the current study, graduates were required to self-assess their preparedness for practice; self-assessment (or selfevaluation) needs to progress through various stages. 10 Arguably, new pharmacy graduates have started only recently on the journey of professional self-assessment and may be inexperienced in its application. Characteristics reported to influence self-assessed competence include age and gender, with younger females perceiving themselves as more competent than older pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…We must therefore ask ourselves whether first-year undergraduates can be expected to have any self-assessment ability. A recent study by Sharif et al [12] showed that at a macro level, where learners were asked to predict their end-of-year and end-of-course results in comparison with their classmates, first-year MPharm students do not have good self-assessment skills. However, it could be argued that such prediction merely constitutes calculating summative achievement to date and factoring in intention of future commitment to study, rather than selfassessing by evaluating current skills and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…We must therefore ask ourselves whether first‐year undergraduates can be expected to have any self‐assessment ability. A recent study by Sharif et al 12 . showed that at a macro level, where learners were asked to predict their end‐of‐year and end‐of‐course results in comparison with their classmates, first‐year MPharm students do not have good self‐assessment skills.…”
Section: Discussionmentioning
confidence: 99%